Complications and safe prescription of interventions for adult sleep disordered breathing in Australia - Love, Rachelle L.; Naughton, Matthew T.; Cistulli, Peter; McArdle, Nigel; MacKay, Stuart G. (Australian Journal of Otolaryngology; Vol 2 (March 2019): Australian Journal of Otolaryngology, 2019)
The American Academy of Sleep Medicine (AASM) identifies continuous positive airway pressure (CPAP), mandibular advancement splint (MAS), adjunctive medical therapy and surgical modifications of the upper airway potential treatment modalities in adult sleep breathing disorders and promotes a number of Guidelines and Consensus Statements to outline the role of such therapies. Specific treatments under each of these “intervention guidelines” are highlighted as standard, option or guideline with stringent literature analyses supporting each—by derivation, treating clinicians in relevant sleep disciplines should be highly trained and credentialed. Unfortunately, in Australia and elsewhere, sleep disorders, including sleep disordered breathing (SDB), are increasingly being managed by those without the necessary training or expertise, and “pop up” sleep clinics are bypassing comprehensive clinician assessment. This Symposium-derived paper highlights the risks and technical considerations related to each category of available intervention. This paper represents the first time such a focus has been published and incorporates CPAP, MAS, medical therapy and surgery in the same document. This paper explores in detail the complications associated with each of the interventions, and emphasises the requirement for meticulous training and experience to predict, identify, manage and resolve all relevant occurrences. The paper is a summation and expansion of proceedings from the Opening Plenary of the Australasian Sleep Association Scientific Conference from October 2017, and features the four key presentations of Professor Matthew Naughton, Professor Peter Cistulli, Associate Professor Nigel McArdle and Professor Stuart MacKay.